2015
DOI: 10.1590/1981-38212014000200011
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Political Participation in the Americas and the Caribbean

Abstract: This article deals with an issue as yet little explored in the vast literature about political participation: the role of corruption in political engagement. It investigates whether the coexistence, the values and the perception of citizens in relation to corrupt practices and actors have effects on political activism, and it verifies the direction in which this is evolving, whether it is in the direction of engagement in or withdrawal from politics. The unit of analysis is the individual, the geographic secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
7
1
2
Order By: Relevance
“…It is therefore easy to see why perceptions of corruption are likely to affect ordinary citizens to participate in political activities. In recent years, several studies have explored the link between corruption perceptions and various forms of political participation (Bauhr and Grimes 2014;Bonifácio and Paulino 2015;Dahlberg and Solevid 2016;Kostadinova and Kmetty 2019;Miles 2015;Sundström and Stockemer 2015). Nevertheless, there is no agreement on how they are linked, especially when it comes to political participation between elections.…”
Section: Corruption Gender and Political Participation In Democraciesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore easy to see why perceptions of corruption are likely to affect ordinary citizens to participate in political activities. In recent years, several studies have explored the link between corruption perceptions and various forms of political participation (Bauhr and Grimes 2014;Bonifácio and Paulino 2015;Dahlberg and Solevid 2016;Kostadinova and Kmetty 2019;Miles 2015;Sundström and Stockemer 2015). Nevertheless, there is no agreement on how they are linked, especially when it comes to political participation between elections.…”
Section: Corruption Gender and Political Participation In Democraciesmentioning
confidence: 99%
“…Other studies indicate that clientelistic strategies have an important gender dimension in that men are often their principal targets while women tend to be excluded from them (Vicente and Wantchekon 2009;Wantchekon 2003). Bonifácio and Paulino (2015) and Kostadinova and Kmetty (2019) show that experiences with corruption increase the likelihood of engagement, at least with regard to nonelectoral forms of participation. These findings suggest that the mobilizing effect of corruption perceptions is higher in contexts where petty corruption is more common, and perceptions are more closely related to actual experiences.…”
Section: Corruption Gender and Political Participation In Democraciesmentioning
confidence: 99%
“…Thus, an individual with party affiliation generally believes that a party they associate with performs more effectively and efficiently than other parties (Jacob & Schenke, 2020;Wilkes, 2015). Regarding the possible relationship between political participation and political trust, past studies (Bonifácio & Paulino, 2015;Wilkes, 2015) found that party affiliation, tolerance, for and experience with corruption determined people's trust in the incumbent government. Hence, we propose that:…”
Section: Political Participation and Politicalmentioning
confidence: 99%
“…For a broader picture of how corruption affects political participation, it is important to have a better understanding of corruption. The authors of a study focused on Latin American countries using the AmericasBarometer distinguish between the perception, experience, and tolerance of corruption (Bonifácio and Paulino 2015). These elements are evaluated at the individual level, based on respondents' answers to the survey.…”
Section: Influence Of Corruption On Institutionalized and Non-institumentioning
confidence: 99%